Natural distemper infection in stone martens (Martes foina): From infection to neutralizing antibodies. (September 2021) - Balboni, Andrea; Savini, Federica; Scagliarini, Alessandra; Berti, Elisa; Naldi, Marzia; Urbani, Lorenza; Fontana, Maria Cristina; Carra, Elena; Gibelli, Lucia Rita Maria; Gobbo, Federica; Bologna, Emanuela; Zambelli, Donatella; et al.
Abstract: We report an outbreak of canine distemper virus (CDV) among stone martens ( Martes foina ) in Italy. After being rescued in Northern Italy between April and June 2018, six subjects were kept in a wildlife and exotic animal rescue center in Bologna province. Subjects have been monitored for 15 months in captivity. Within this time-lapse, two subjects died, while among the remaining four, only one showed clinical symptoms referable to distemper. Surviving subjects have been regularly tested for CDV by means of reverse transcriptase-PCR from conjunctival and oropharyngeal swabs for eleven months. The identified viruses belonged to the Wildlife-Europe CDV genetic subgroup. Neutralizing antibodies were detected at the end of the eleven months, when all subjects tested reverse transcriptase-PCR negative. Our findings confirm the circulation of the Wildlife-Europe CDV genetic subgroup (Europe 1/South America 1 lineage) within the Italian wildlife, and improve knowledge on viral infection in stone martens. Highlights: CDV outbreak reported in stone martens in an wildlife rescue center. Among six, two subjects died, one showed clinical signs, three were asymptomatic. Viral RNA excretion was demonstrated for at least five months in surviving subjects. The identified viruses belonged to the Wildlife-Europe genetic subgroup. After eleven months, sero-neutralization revealed neutralizing antibodies.